2016
DOI: 10.1136/annrheumdis-2016-209958
|View full text |Cite
|
Sign up to set email alerts
|

Effects of bariatric surgery on gout incidence in the Swedish Obese Subjects study: a non-randomised, prospective, controlled intervention trial

Abstract: Objectives To assess the long-term effect of bariatric surgery on the incidence of gout and hyperuricemia in participants of the Swedish Obese Subjects (SOS) study. Methods This report includes 1982 subjects who underwent bariatric surgery and 1999 obese controls from the SOS study, a prospective intervention trial designed to assess the effect of bariatric surgery compared with conventional treatment. None of the subjects had gout at baseline. An endpoint on gout incidence was created based on information o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
40
0
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 71 publications
(51 citation statements)
references
References 43 publications
3
40
0
8
Order By: Relevance
“…The Swedish Obese Subjects (SOS) study is a longitudinal controlled study on the effect of bariatric surgery on mortality and on the incidence of obesity-related diseases [ 15 , 16 ]. We have recently shown that, in individuals with obesity, bariatric surgery associates with a lower risk of developing gout and psoriasis, two common inflammatory diseases [ 17 , 18 ]. The aim of this study was to determine whether bariatric surgery associated with a lower incidence of RA in SOS study participants.…”
Section: Introductionmentioning
confidence: 99%
“…The Swedish Obese Subjects (SOS) study is a longitudinal controlled study on the effect of bariatric surgery on mortality and on the incidence of obesity-related diseases [ 15 , 16 ]. We have recently shown that, in individuals with obesity, bariatric surgery associates with a lower risk of developing gout and psoriasis, two common inflammatory diseases [ 17 , 18 ]. The aim of this study was to determine whether bariatric surgery associated with a lower incidence of RA in SOS study participants.…”
Section: Introductionmentioning
confidence: 99%
“…Our hypothetical scenarios are consistent with previous studies that examined the effect of weight change on gout. Studies on the effects of weight-loss interventions from either bariatric surgery or lifestyle modi cation are associated with reduced incidence of gout 28,31,32,33 . A systematic review 34 shows that a weight loss of >3.5 kg showed bene cial effects on gout attacks at mediumterm/long-term follow-up.…”
Section: Comparison Between Previous Studies and Our Resultsmentioning
confidence: 99%
“…In einer prospektiven kontrollierten schwedischen Studie wurde gezeigt, dass die Inzidenz einer Hyperurikämie nach bariatrischer OP im Vergleich zu konventionell therapierten Patienten über ein Follow-up von 15 Jahren signifikant geringer war [33]. Dies ging mit einer signifikanten Abnahme des Gicht-Risikos einher (HR 0,6; 95 %-KI: 0,48-0,75).…”
Section: Fruktoseunclassified